Novel Non-phosphorylated Serine 9/21 GSK3β/α Antibodies: Expanding the Tools for Studying GSK3 Regulation - Grabinski, Tessa; Kanaan, Nicholas M. (Frontiers in Molecular Neuroscience, 2016)
Glycogen synthase kinase 3 (GSK3) and are serine/threonine kinases involved in many biological processes. A primary mechanism of GSK3 activity regulation is phosphorylation of N-terminal serine (S) residues (S9 in GSK3b, S21 in GSK3a). Phosphorylation is inhibitory to GSK3 kinase activity because the phosphorylated N-terminus acts as a competitive inhibitor for primed substrates. Despite widespread interest in GSK3 across most fields of biology, the research community does not have reagents that specifically react with nonphosphoS9/21 GSK3a/b (the so-called “active” form). Here, we describe two novel monoclonal antibodies that specifically react with nonphosphoS9/21 GSK3a/b in multiple species (human, mouse and rat). One of the antibodies is specific for nonphospho-S9 GSK3b (clone 12B2) and one for nonphospho-S9/21 GSK3a/b (clone 15C2). These reagents were validated for specificity and reactivity in several biochemical and immunochemical assays, and they show linear detection of nonphosphoS GSK3. Finally, these reagents provide significant advantages in studying GSK3 regulation. We used 12B2 (due to its specificity for GSK3bs) to study the regulation of S9 phosphorylation by Akt and protein phosphatases, and to demonstrate that protein phosphatase inhibition reduces nonphospho-S9 GSK3b levels and lowers kinase activity within cells. The ability to use the same reagent across biochemical, immunohistological and kinase activity assays provides a powerful approach for studying serine-dependent regulation of GSK3a/b.